Predicting factor analysis of postoperative complications after robot‐assisted radical cystectomy: Multicenter KORARC database study. (8th February 2022) - Kim, Hwanik; Jeong, Byong Chang; Lee, Sangchul; Ku, Ja Hyeon; Kwon, Tae Gyun; Kim, Tae‑Hwan; Jeon, Seung Hyun; Lee, Sang Hyub; Nam, Jong Kil; Kim, Wansuk; Lee, Ji Youl; Hong, Sung Hoo; et al.
Abstract : Objectives: To evaluate postoperative complications following robot‐assisted radical cystectomy in patients diagnosed with bladder cancer and reveal if there are predictors for postoperative complications. Methods: Prospectively collected medical records of 730 robot‐assisted radical cystectomy patients between 2007/04 and 2019/05 in 13 tertiary referral centers were reviewed. Perioperative outcomes were compared between two groups by postoperative complications (complication vs non‐complication). We assessed recurrence‐free survival, cancer‐specific survival, and overall survival between groups. Regression analyses were implemented to identify factors associated with postoperative complications. Results: Any total and high‐grade complication (Clavien–Dindo grade ≥3) rates were 57.8% and 21.1%, respectively. Patients in complication group had significantly higher proportion of diabetes mellitus ( P  = 0.048), chronic kidney disease ( P  = 0.011), dyslipidemia ( P  < 0.001), longer operation time ( P  = 0.001), more estimated blood loss ( P  = 0.001), and larger intraoperative fluid volume ( P  < 0.001). There was a significant difference in cancer‐specific survival (log‐rank P  = 0.038, median cancer‐specific survival: both groups not reached). Dyslipidemia (odds ratio 2.59, P  = 0.002) and intraoperative fluid volume (odds ratio 1.0002, P  = 0.040) were significantly associated with high‐grade postoperative complications. Diabetes mellitus (odds ratio 1.97, P  = 0.028), chronic kidney disease (odds ratio 1.89, P  = 0.046), dyslipidemia (odds ratio 5.94, P  = 0.007), and intraoperative fluid volume (odds ratio 1.0002, P  = 0.009) were significantly associated with any postoperative complications. Conclusions: Patients with diabetes mellitus, chronic kidney disease, dyslipidemia, or a relatively large intraoperatively infused fluid volume are more likely to develop postoperative complications. Patients with postoperative complications might have a possibility of lower cancer‐specific survival rate.